KELAYAKAN USAHATANI TEMBAKAU VIRGINIA: STUDI KOMPARASI PADA PROSES PENGOVENAN DI KABUPATEN LOMBOK TIMUR - Muhammad Anwar; Rini Endang Prasetyowati; Hidayatul Ahyani (JSEP (Journal of Social and Agricultural Economics), 2021)
There are two methods of flue curing process used in virginia tobacco farmers in East Lombok, which are curing with fossil fuel and curing with local (alternative) fuels (candlenut shell, palm kernel shells, wood, and corn cobs). Now days, due to increasing fossil fuels price, farmer tend to use local fuels. The research objective was to compare the costs, income, and feasibility level of virginia tobacco farming on the use of various alternative fuels in the oven process in East Lombok Regency. The method used is descriptive survey method to 40 farmers. The cost of farming virginia tobacco using candlenut shell as fuel is Rp. 44,788,057/ha/planting season with an R/C ratio of 1.6 palm kernel shells of 45,081,109/ha/planting season with an R/C ratio of 1.5 wood of Rp. 49,498,452/ha/planting season with an R/C ratio of 1.4 and corn cobs of Rp. 39,184,196/ha/planting season with an R/C ratio of 1.8. The highest income is obtained from farmers who use corn cobs as fuel of Rp. 30,037,854/ha/planting season, the income of the farmers who use hazelnut shell and palm shell as fuel each is Rp. 25,938,788/ha/planting season and Rp. 23,757,891/ha/planting season. The lowest income using wood fuel is Rp. 16,883,748/ha/planting season. Because the R/C value is more than 1, it means that virginia tobacco farming using various alternative materials in the oven process in East Lombok Regency is feasible.